Supramolecular Nanotubules as a Catalytic Regulator for Palladium Cations: Applications in Selective Catalysis. (9th August 2017) - Wu, Shanshan; Li, Yongguang; Xie, Siying; Ma, Cong; Lim, Joonwon; Zhao, Jiong; Kim, Dae Seok; Yang, Minyong; Yoon, Doong Ki; Lee, Myongsoo; Kim, Sang Ouk; Huang, Zhegang
Abstract: Despite the recent development of highly efficient and stable metal catalysts, conferral of regulatory characteristics to the catalytic reaction in heterogeneous systems remains a challenge. Novel supramolecular nanotubules were prepared by alternative stacking from trimeric macrocycles, which was found to be able to coordinate with Pd cations. The Pd complexes exhibited a high catalytic performance for C−C coupling reaction. Notably, the tubular catalyst was observed to be controlled by supramolecular reversible assembly and showed superior heterogeneous catalytic activity, which was maintained for a number of cycles or reuse under an aerobic environment. Furthermore, the supramolecular catalyst showed unprecedented selectivity for the multifunctional coupling reaction and was able to serve as a new constructor of asymmetrical compounds.